Bacteria contribute to pesticide degradation in cryoconite holes in an Alpine glacier. (November 2017) - Ferrario, Claudia; Pittino, Francesca; Tagliaferri, Ilario; Gandolfi, Isabella; Bestetti, Giuseppina; Azzoni, Roberto Sergio; Diolaiuti, Guglielmina; Franzetti, Andrea; Ambrosini, Roberto; Villa, Sara
Abstract: Organic contaminants deposited on glacier snow and ice are subject to partitioning and degradation processes that determine their environmental fate and, consequently, their accumulation in ice bodies. Among these processes, organic compound degradation by supraglacial bacteria has been investigated to a lesser extent than photo- and chemical degradation. We investigated biodegradation of the organophosphorus insecticide chlorpyrifos (CPF), a xenobiotic tracer that accumulates on glaciers after atmospheric medium- and long-range transport, by installing in situ microcosms on an Alpine glacier to simulate cryoconite hole systems. We found that biodegradation contributed to the removal of CPF from the glacier surface more than photo- and chemical degradation. The high concentration of CPF (2–3 μg g −1 w.w.) detected in cryoconite holes and the estimated half-life of this compound (35–69 days in glacier environment) indicated that biodegradation can significantly reduce CPF concentrations on glaciers and its runoff to downstream ecosystems. The metabolic versatility of cryoconite bacteria suggests that these habitats might contribute to the degradation of a wide class of pollutants. We therefore propose that cryoconite acts as a "biofilter" by accumulating both pollutants and biodegradative microbial communities. The contribution of cryoconite to the removal of organic pollutants should be included in models predicting the environmental fate of these compounds in cold areas. Graphical abstract: Highlights: Unlike photo- and chemical degradation, biodegradation of organic compounds by supraglacial bacteria has been neglected. In situ microcosm experiments showed that the pesticide chlorpyrifos can be efficiently biodegraded on mountain glaciers. Biodegradation should be included in models predicting the environmental fate of organic pollutants in cold areas. Abstract : Biodegradation significantly contributes to the removal of pesticide from glaciers, thus environmental fate models of pesticides in glacierized areas should account for this process.